Importance of Cardiopulmonary Exercise Testing amongst Subjects Recovering from COVID-19 - Dorelli, Gianluigi; Braggio, Michele; Gabbiani, Daniele; Busti, Fabiana; Caminati, Marco; Senna, Gianenrico; Girelli, Domenico; Laveneziana, Pierantonio; Ferrari, Marcello; Sartori, Giulia; Dalle Carbonare, Luca; Crisafulli, Ernesto (Diagnostics (Basel), 2021)
The cardiopulmonary exercise test (CPET) provides an objective assessment of ventilatory limitation, related to the exercise minute ventilation (VE) coupled to carbon dioxide output (VCO2) (VE/VCO2); high values of VE/VCO2 slope define an exercise ventilatory inefficiency (EVin). In subjects recovered from hospitalised COVID-19, we explored the methodology of CPET in order to evaluate the presence of cardiopulmonary alterations. Our prospective study (RESPICOVID) has been proposed to evaluate pulmonary damage’s clinical impact in post-COVID subjects. In a subgroup of subjects (RESPICOVID2) without baseline confounders, we performed the CPET. According to the VE/VCO2 slope, subjects were divided into having EVin and exercise ventilatory efficiency (EVef). Data concerning general variables, hospitalisation, lung function, and gas-analysis were also collected. The RESPICOVID2 enrolled 28 subjects, of whom 8 (29%) had EVin. As compared to subjects with EVef, subjects with EVin showed a reduction in heart rate (HR) recovery. VE/VCO2 slope was inversely correlated with HR recovery; this correlation was confirmed in a subgroup of older, non-smoking male subjects, regardless of the presence of arterial hypertension. More than one-fourth of subjects recovered from hospitalised COVID-19 have EVin. The relationship between EVin and HR recovery may represent a novel hallmark of post-COVID cardiopulmonary alterations.